Educational manual for prevention and control of rhabdomyolysis in military physical exercises (Research, Society and Development, 2022)
Objective: Develop, validate and legitimize an Educational Manual for Prevention and Control of Rhabdomyolysis in Military Physical Exercises. Method: A literature review was carried out in the main Health Sciences databases; textual elaboration; choice of illustrations; spell check; manual layout; expert consultation; consultation with the target audience; validation and legitimation by specific questionnaires; in the statistical analysis, Cronbach's Alpha (α) and Chi-square tests were used, with a Content Validity Index of 100%. Results: The manual has been validated and legitimized, demonstrating the reliability that the questionnaires presented, reaching the result of α=0.8495 in the validation and α=0.9337 in the legitimation and Chi-square test p